INCREASING STUDENTS CLASSROOM PARTICIPATION USING WHATSAPP - Nurrochim Abdulloh; Karmadi Karmadi; Sri Iswahyuni; Rahma Yuniarti (Universitas Duta Bangsa Surakarta, 2024)
WhatsApp is expected to increase students' active participation in learning English, and this article aims to show the role of it. This research uses collaborative Classroom Action Research using the Kemmis and Mc Taggart model. It was carried out at STIKES Mambaul 'Ulum Surakarta in the D3 Nursing Study Program in the second semester of the 2023/2024 academic year. The research subjects were 34 students. The object of research is active student participation. This research was conducted in 2 cycles, and each cycle contained 3 meetings, each cycle was conducted in 4 stages, namely planning, action, observation and reflection, while the research instruments were observation sheets and field notes. Data collection techniques were carried out using observation, interviews and documentation. The results of the research show that from pre research to cycle 1 there is improvement for 10.58%; and from cycle 1 to cycle 2, the improvement is 24.33%. It means the use of the WhatsApp application in English language learning in the D3 Nursing study program Stikes Mamba'ul 'ulum Surakarta, second semester can increase students' active participation. This is proven by the results of the research showing that in cycle I, there were several students who were less active, in cycle II, there was a significant increase in students' classroom participation.